Penerapan Artificial Intelligence Pada Sistem E-Learning Di Perguruan Tinggi - Erika Putri Say; Novan Wijaya (JOURNAL SAINS STUDENT RESEARCH, 2026)
The use of artificial intelligence (AI) in online learning (e-learning) systems at universities is currently a critical topic, as traditional systems are considered too one-sided and unable to adequately accommodate the unique learning styles of individual students. However, if not carefully managed, the use of AI could threaten the security of students’ personal data and undermine their ability to think critically. This study aims to summarize and map out the best strategies to ensure that the implementation of AI on campus can proceed safely, effectively, and fairly. The method used in this study is a Systematic Literature Review (SLR), which examined 10 indexed scientific articles published from 2020 to 2026. The results show that AI has been proven to help students by increasing their daily self-study hours by up to 52% and raising their average exam scores by 15%. On the other hand, excessive reliance on AI also has negative consequences, such as making students reluctant to think critically, increasing the risk of cheating or plagiarism, creating vulnerabilities to data breaches online, and reducing face-to-face social interaction on campus. As a solution, universities are advised to strengthen their cybersecurity systems, shift from rote-memorization exams to practical assessments such as e-portfolios and group project assignments, and improve faculty members’ digital teaching skills.